PRAGMALINGUODIDACTIC CHALLENGES: ENHANCING COMMUNICATION STRATEGIES IN LANGUAGE TEACHING (American Journal of Pedagogical and Educational Research, 2023)
This study delves into the intricate landscape of language education, exploring the pragmatic, linguistic, and didactic challenges faced by educators in fostering effective communication skills. Pragmatic challenges, including politeness and cultural nuances, linguistic complexities encompassing grammar and vocabulary variations, and didactic hurdles related to teaching methodologies, constitute the focal points of analysis. The study advocates for a holistic approach, emphasizing the interrelated nature of these challenges and proposing innovative, adaptive teaching strategies. By addressing these multifaceted obstacles, educators can create inclusive, culturally sensitive learning environments, fostering proficient and confident language learners.